Sex of First Child and Actual Fertility Among Vietnamese Women from Generations X, Y, and Z: Examining Intergenerational Patterns of Son Preference - Nguyen, Yen Thi Hai; Dang, Truc Ngoc Hoang; Sukontamarn, Pataporn; Lai, Siow-Li; Pechdin, Watchara (Journal of Population and Social Studies [JPSS], 2025)
Drawing on data from the 2020–21 Vietnam Multiple Indicator Cluster Survey (MICS), which includes 7,813 women from Generations X, Y, and Z, this study makes a unique contribution by applying survival analysis to examine intergenerational shifts in son preference—an approach not previously applied, to our knowledge. The analysis investigates how the sex of the first child affects both the likelihood and timing of subsequent children. The findings reveal that son preference persists, with Generation Z demonstrating a stronger inclination toward having sons compared to Generations X and Y, despite Vietnam’s notable economic progress and policy efforts to address gender imbalance. This persistent pattern likely reflects deeply rooted institutional and cultural norms that favor male offspring. As a result, women may feel compelled to continue childbearing until a son is born, driven by the belief that sons offer better social and economic prospects. These insights highlight the urgent need for more targeted policy interventions to challenge the cultural son preference, especially in the context of Vietnam’s declining fertility rates.